Pemberdayaan UMKM Berbasis Digital : Strategi Pemasaran, Penguatan Merek, dan Legalitas Usaha dan Pengembangan Kapasitas Digital - Anisa Nur Aziizah; Budi Susanto; Salsabilla Ramadhani; Anisa Al-Mas; Akbar Hermansyah; Nurhayati Suarga (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This Micro, Small, and Medium Enterprises (MSMEs) assistance program aims to improve business capacity, strengthen branding, expand marketing reach, and provide formal legal status to MSMEs. Activities carried out include digital marketing training, assistance in creating e-commerce accounts, designing and delivering MSME logos, providing grants for sealing equipment, and assisting in obtaining a Business Identification Number (NIB) through the OSS system. The implementation methods include initial observation, activity planning, interactive training, direct mentoring, and post-activity monitoring and evaluation. These methods are designed to ensure that MSMEs are not only equipped with technical knowledge but also empowered with the practical tools necessary for success in a competitive market. The results of the activities show an improvement in the digital marketing skills of MSMEs, allowing them to reach a wider audience through social media platforms and online advertising. The creation of logos as brand identities has significantly boosted the recognition of these businesses, helping them establish a stronger presence in their respective markets. Additionally, the enhanced product packaging quality with the provision of sealing tools has led to better product presentation, which is essential in attracting customers and increasing sales. Furthermore, the acquisition of NIBs as business legal status has provided MSMEs with greater legitimacy, enabling them to access more formal business opportunities and funding options. This program has had a positive impact on the professionalism and competitiveness of MSMEs, which has been reflected in their increased ability to market their products effectively and efficiently. However, further assistance is needed in optimizing digital promotion, such as improving online advertising strategies, and fully utilizing NIBs for better business expansion. Moreover, it is crucial to offer ongoing support and guidance to ensure that MSMEs can continue to thrive and adapt to the rapidly changing digital landscape